STUDI KOMPARASI HASIL BELAJAR SISWA MELALUI MODEL TEAM GAMES TOURNAMENT DENGAN TWO STAY TWO STRAY DI KELAS XI - Nuriza, Nuriza; Sulistyarini, Sulistyarini; Hari Christanto, Ludovicus Manditya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine differences in student learning outcomes in geography learning through the team games tournament model with two stay two strays in class XI of Muhammadiyah 1 Pontianak High School. The research method used is an experimental method with a quantitative approach. The design of this study is non equivalent control group design consisting of several stages, namely the preparation stage, preparation of learning tools, and research instruments. The implementation phase and the final stage are the implementation of learning, data analysis and report generation. Based on calculations obtained the average results of the final test in the experimental class I was 74 and the average final test in the experimental class II was 70. The results of the hypothesis test using separated variance namely tcount> ttable (2.05> 2.00) meant Ha was accepted . So, it can be concluded that there is a significant difference between the average learning outcomes of students who use the team games tournament model with two stay two strays in class XI of Muhammadiyah 1 Pontianak High School. This research can be used as an alternative to improving learning models both geography and other lessons.Keywords: Learning Outcomes, Team Games Tournament Model, Two Stay Two Stray,